Improving The Performance of SMES Through the Integration of An E-Commerce Adoption Success Model Based on Technological Frames of References and Knowledge Management - R.A. Nurlinda; Eka Bertuah; Ari Anggarani WPT (Ebiz Prima Nusa, 2024)
The existence of micro, small, and medium enterprises (MSMEs) in Indonesia is important because their existence makes a big contribution, especially to economic growth, job creation, and poverty alleviation. The increasingly rapid development of information technology has also had an influence on the development of MSMEs in Indonesia, especially in the application of e-commerce to market products and the increased competitiveness of MSMEs with other businesses. This research aims to identify the influence of e-commerce adoption on MSME performance based on technological frames of reference and knowledge management, which are used to evaluate the relationship between variables. The sample in this research is 200 MSMEs that already use e-commerce in the JABODETABEK area. This research uses Structural Equation Modeling Type Partial Least Squares (SEM-PLS). The research results show that Technological Frames of References have a positive effect on E-commerce Adoption, but Knowledge Management has no effect on e-commerce adoption. The results of further research show that Technological Frames of References, Knowledge Management and e-commerce adoption influence the performance of MSMEs. The results of this evaluation can be a guide for MSMEs to improve their performance through e-commerce adoption so that they can build strong relationships with existing customers and attract new customers.